Prevalence of patients with self‐reported hidradenitis suppurativa in a cohort of Danish blood donors: a cross‐sectional study. (1st April 2019) - Theut Riis, P.; Pedersen, O.B.; Sigsgaard, V.; Erikstrup, C.; Paarup, H.M.; Nielsen, K.R.; Burgdorf, K.S.; Hjalgrim, H.; Rostgaard, K.; Banasik, K.; Ullum, H.; Jemec, G.B.
Summary: Background: Hidradenitis suppurativa (HS) is a chronic inflammatory skin disease characterized by recurrent inflamed nodules. No pathognomonic test is available for HS; hence the diagnosis is based on three clinical criteria. Objectives: To estimate the cross‐sectional prevalence and characterize patients with HS in the Danish Blood Donor Study cohort. Methods: A questionnaire previously developed containing HS screening questions, the Major Depression Inventory, the Short Form‐12, as well as questions about height, weight and drinking habits was answered by 27 765 blood donors. Results: The prevalence of HS was 1·8% [95% confidence interval (CI) 1·6–2·0%] in the cohort of Danish blood donors. Donors with HS were on average 4·7 years younger ( P < 0·001), had 1·3 kg m −2 higher mean body mass index (BMI) ( P < 0·001) and were significantly more likely to smoke [odds ratio (OR) 1·44, 17·9% vs. 13·1%, P = 0·002] compared with donors without HS. Furthermore, significantly more donors with HS were classified as having moderate depression (3·2% vs. 0·7%, P < 0·001). Also, significantly more patients with HS were apprenticeship educated, received educational support and sickness or cash benefits. Conclusions: The prevalence of HS in the cohort of blood donors was estimated to 1·8% (95% CI 1·6–2·0%). Donors with HS reported characteristics similar to those reported for hospital‐based patients with HS such as higher BMI, smoking rates and lower socioeconomic status than donors without HS.